Caribou Co-Management Needs From Research: Simple questions - Tricky answers - Urquhart, Doug (Rangifer, 1996)
Over the past decade, northern Canada has experienced a substantial increase in government reliance on advisory co-management organizations to manage caribou populations. Such groups, which are usually composed of government and local representatives, constantly require information about caribou upon which to base their recommendations. However, the standard 'scientific' approach to obtaining and presenting such information is in many cases no longer appropriate. In order to readjust the scientific focus on caribou research so that it is better attuned to co-management, this paper examines the role that research plays in the Canadian management of the Porcupine Caribou Herd as practiced by the Porcupine Caribou Management Board - a co-management advisory organization with a majority of native representatives.